Communicative-functional components of discourse - Shapran, Nataliia V.; Novoseletska, Svitlana V.; Koliada, Elina K.; Musiichuk, Tetiana I.; Simak, Kateryna V. (Linguistics and Culture Review, 2021)
The article considers the main types of semantic-sigmatic and communicative-functional transformations of lexical units against the background of changes in certain parameters of discourse and analyzes the fundamental motives for changing the load of lexical units in modern space. The relevance of this work is determined by modern transformations of linguistic study of different types of discourse, which occur on the basis of the study of communication and the search for universal foundations of linguistic interaction. Language is considered as a complex communicative and cognitive phenomenon that determines the state of intercultural communication. The components that directly affect the communication process and the success of the modern language formation must be identified. The aim of this study was to analyze the semantic-sigmatic and communicative-functional components of discourse and the theory of their understanding in modern communication. The theoretical and methodological basis of the study included the works of scientists in the field of modern methods of communication. The objective method was the analysis of documents (monographs, articles, statistics, scientific papers and textbooks on the selected topic).